Studi Deskriptif Tim Paduan Suara SD Negeri 01 Kota Bengkulu Dalam Konteks Musikalitas - Rizki Nur Fadhilah; Bambang Parmadie; Pebrian Tarmizi (Universitas Bengkulu, 2021)
The purpose of this study was to determine the musicality of the elementary school choir team 01 Bengkulu City. The research method used is descriptive qualitative method. The subject of this research was the choir team from the 01 Elementary School of Bengkulu City. The instruments used were observation and interviews. Data collection techniques using observation, interviews, and documentation. The data obtained were analyzed through the Miles, Huberman, and Saldana models, namely data collection, data condensation, data display, and data verification. The results of this study are the musicality of the choir team's performance at the State Elementary School 01 Bengkulu City is still not maximal, which is due to disciplinary aspects, inadequate performance aspects and inadequate implementation of supporting facilities for the choir team's activities, especially the absence of competent trainers music especially in the choir field.